Ethnic business: mainstream and outsider traditions of tamil entrepreneurship - Ananda, A.S. (University of Jaffna, 2014)
This paper challenges traditional as well as homogenous scales of appraising ethnic entrepreneurship that exists in concurrent ethnic entrepreneurship literature, with paying attention to diverge and dynamic characteristics of Tamil entrepreneurship. It emphasizes that the Tamil business may classify into several factions as far as mobilizing different peculiarities of each sub profile without narrowing down one group as “Tamil entrepreneurship”. Therefore the study has cast a new gaze upon comparing entrepreneurialism of ‘outsider’ entrepreneurs and mainstream business groups. For instance, the Chettiars and the Muslim Tamils, who are mainly Tamilnadu, Jaffna and Colombo based Tamils, represent the mainstream of the worldwide ethnic commercial network of Tamils. Their particular identity is likely to be on account of both primordial and situational aspects of ethnic entrepreneurship. On the other hand, the entrepreneurial mobility of the bottom level of the Up-country Tamils shows particular characteristics of the ‘outsiders’ of business. The initiation of the Upcountry Tamil business from micro level is greatly dependent on the unlimited dedication of an entrepreneur. The research has entirely based on literature on Tamil business communities worldwide undertaken into historical analysis scheme. Therefore, this paper will be important in terms of widening theoretical approaches of ethnic entrepreneurship by emphasizing the need of multiple approaches to comprehend each sub section of an ethnic group.
Keywords: Ethnic entrepreneurship; Tamil business; Mainstream; Outsider traditions